Signal optimization in inhomogeneous fields: application of quantum optimal control theory troy - Borneman, Troy W.; Cory, David G.; Hürlimann, Martin D. (Diffusion Fundamentals, 2009)
We demonstrate that pulses derived using Optimal Control Theory (OCT) techniques can be used to significantly enhance the robustness of the Carr-Purcell-Meiboom-Gill sequence (CPMG) [1,2] to inhomogeneities in the static BB0 field. By numerically inverting the Liouville - von Neumann equation, OCT pulses were derived that can be used directly in place of hard pulses in the CPMG sequence to greatly improve the bandwidth of refocusing. To retain the echo stability achieved by the Meiboom-Gill correction to the Carr-Purcell sequence, the refocusing pulses were designed to perform a unitary π-rotation as opposed to just a state inversion transfer. To illustrate this approach we present an example of optimized pulses that show an improved CPMG-like behavior with complete excitation and multiple refocusing over a bandwidth of +/- 2.6 γB1,max B with a pulse duration limited to 10 t180.